Motivational impact of active learning methods in aerospace engineering students. (December 2019) - López-Fernández, Daniel; Ezquerro, José Miguel; Rodríguez, Jacobo; Porter, Jeff; Lapuerta, Victoria
Abstract: Motivation is a critical factor in academic performance. In the case of aerospace engineering education, it is particularly necessary due to the difficulty of the subject, so it is essential to use reliable instruments to allow aerospace engineering teachers to understand how their students' motivation works. Moreover, it is important to identify educational techniques that enhance the motivation of aerospace engineering students and help them to persevere through a challenging workload. In this contribution, the motivation of students of the Master of Aerospace Engineering degree of the Universidad Politécnica de Madrid is analyzed in two subjects that use different educational techniques. A teaching centered approach is applied in one subject, while active learning methods like Project Based Learning are applied in the other. In this second approach, students are required to perform a preliminary design of a Space Mission starting from Mission requirements and must integrate the subsystems of a microsatellite using demonstration satellites. A reliable instrument tailored for engineering students has been used during two academic years to evaluate the impact of these techniques on the students' motivation. The empirical experience described here confirms the positive impact of active learning methods and indicates the key factors, both intrinsic and extrinsic, in the motivation of aerospace engineering students. Highlights: Aerospace students' motivation factors are assessed through a tested instrument. Active learning methods help to develop both intrinsic and extrinsic motivators. Impact of classical and active learning methods in aerospace students' motivation.